2018
DOI: 10.1016/j.jacc.2018.09.073
|View full text |Cite
|
Sign up to set email alerts
|

His Resynchronization Versus Biventricular Pacing in Patients With Heart Failure and Left Bundle Branch Block

Abstract: BackgroundHis bundle pacing is a new method for delivering cardiac resynchronization therapy (CRT).ObjectivesThe authors performed a head-to-head, high-precision, acute crossover comparison between His bundle pacing and conventional biventricular CRT, measuring effects on ventricular activation and acute hemodynamic function.MethodsPatients with heart failure and left bundle branch block referred for conventional biventricular CRT were recruited. Using noninvasive epicardial electrocardiographic imaging, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
143
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(158 citation statements)
references
References 29 publications
(44 reference statements)
7
143
0
8
Order By: Relevance
“…HBP produces a narrow QRS duration and, by preserving physiological ventricular activation, may prevent the development of right ventricular pacing‐induced cardiomyopathy in patients with a bradycardia indication for pacing . Furthermore, HBP can often correct bundle branch block, resulting in a reduction in QRS duration and improvement in ventricular activation time …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HBP produces a narrow QRS duration and, by preserving physiological ventricular activation, may prevent the development of right ventricular pacing‐induced cardiomyopathy in patients with a bradycardia indication for pacing . Furthermore, HBP can often correct bundle branch block, resulting in a reduction in QRS duration and improvement in ventricular activation time …”
Section: Introductionmentioning
confidence: 99%
“…2 Furthermore, HBP can often correct bundle branch block, resulting in a reduction in QRS duration and improvement in ventricular activation time. 3 The HBP pioneers encountered several challenges during the early years of HBP, such as low procedural success rates and high and rising thresholds. 1 However, with the arrival of specialized delivery equipment and a more suitable pacing lead, the published HBP success rates appear to have improved.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as illustrated in Figure 5, biventricular pacing only fuses two abnormal wavefronts, whereas HBP restores the normal intrinsic activation leading to less dyssynchrony. Indeed in a recent study by Arnold et al, 23 using noninvasive epicardial electrocardiographic imaging, it was shown that HBP was more effective at delivering ventricular resynchronization and produced greater acute hemodynamic benefit as compared to biventricular pacing. In the recent context of the Partner III 5 and Evolut low risk trials, 4 which included patients with lower risk, the search for better pacing solutions in this population has therefore become crucial.…”
Section: Discussionmentioning
confidence: 99%
“…HBP has been studied by some authors as an alternative to conventional CRT 30–34 and by others in conjunction with CS pacing 35,36 . In an acute hemodynamic study, His resynchronization delivered better ventricular resynchronization and greater improvement in hemodynamic parameters than biventricular pacing 31 . Two small randomized trials comparing HBP alone with conventional CRT did not show a significant clinical benefit of HBP alone vs conventional CRT 32,33 .…”
Section: Discussionmentioning
confidence: 99%